Adapting a safe water storage container to improve household stored water quality in rural Burkina Faso: a cluster randomized trial - Darcy M. Anderson; Michael B. Fisher; Osborn Kwena; Hermann Kambou; Romain Broseus; Ashley R. Williams; Kaida Liang; Rohit Ramaswamy; Jamie Bartram (Journal of Water, Sanitation and Hygiene for Development, 2021)
Safe water storage protects household drinking water from microbial contamination, maintaining water quality and preventing diarrhea and other water-borne diseases. However, achieving high adoption and sustained use of safe storage is challenging. Systematic adaptation can address these challenges by improving contextual fit while retaining core functionality to protect water quality. We applied Plan-Do-Study-Act (PDSA) cycles to systematically adapt a safe water storage container (SWSC) intervention for implementation in rural Burkina Faso. This study describes the adaptation process and the impacts of the SWSC on Escherichia coli contamination in household stored water in a cluster-randomized trial with 49 intervention villages (274 households) and 50 no-intervention control villages (290 households). SWSC adoption among intervention households was high (88.9%). The intervention achieved approximately a 0.4 log reduction in E. coli contamination. Intervention impact was likely moderated by differential changes in improved source use across intervention and control households. Safe storage improves water quality when used consistently. PDSA frameworks can guide the adaptation of safe storage interventions to optimize adoption and sustained use in new contexts while preserving core functions that protect water quality. HIGHLIGHTS Safe water storage interventions can improve health, but uptake and sustained use are challenging.; Adapting storage containers to local preferences and manufacturing abilities improves uptake and sustainability.; Plan-Do-Study-Act cycles are a tool to adapt interventions.; Our adapted safe water storage intervention achieved high sustained use and a significant reduction in microbial contamination of stored drinking water.;